2006
DOI: 10.1186/1471-2180-6-103
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: Different gene expression patterns correlate with the altered phenotype in biofilmassociated bacteria. Iron and iron-linked genes are thought to play a key-role in biofilm formation. The expression of Fe-linked genes (sirR, sitABC operon) in Staphylococcus epidermidis, was compared in planktonic versus sessile bacteria in vitro and in vivo in a subcutaneous foreign body rat model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The sequences of the 38 SBPs included in this study were obtained from the NCBI and had the following GI numbers: AdcA_Spn, GI:116516060 (Bayle et al 2011); AdcAII_Spn, GI:116515739 (Bayle et al 2011; Loisel et al 2008); FimA_Spa, GI:504525723 (Oetjen et al 2002); Lbp_Spy, GI:16151821 (Linke et al 2008; Linke et al 2009); Lmb_Sag, GI:22537388 (Ragunathan et al 2009a; Ragunathan et al 2009b); MntA_Ban, GI:229264967 (Gat et al 2005); MtsA_Sag, GI:22537676 (Bray et al 2009); MtsA_Spy, GI:383493478 (Sun et al 2009; Sun et al 2008); MntC_Ngo, GI:59800624 (Lim et al 2008); MntC_Sau, GI:88194402 (Horsburgh et al 2002a); MntC_Syn, GI:1653002 (Adir et al 2002); MtsA_Sin, GI:343481042 (Zou et al 2010); MtuA_Sub, GI:222113460 (Banerjee et al 2003); PsaA_Spn, GI:116515973 (McDevitt et al 2011); ScaA_Sgo, GI:310633 (Jakubovics et al 2000; Kolenbrander et al 1998); SitA_Eco, GI:84060846 (Sabri et al 2006); SitA_Sen, GI:16761638 (Zhou et al 1999); SitA_Sme, GI:15966779 (Chao et al 2004; Davies and Walker 2007; Platero et al 2004); SitA_Sps, GI:10135086 (Abate et al 2014); SitC_Sep, GI:57636840 (Cockayne et al 1998; Massonet et al 2006); SloC_Smu, GI:8925939 (Paik et al 2003); SsaB_San, GI:153826 (Crump et al 2014); TroA_Ssu, GI:386583456 (Wichgers Schreur et al 2011; Zheng et al 2011); TroA_Tpa, GI:1777933 (Deka et al 1999; Desrosiers et al 2007; Lee et al 1999; Lee et al 2002); YfeA_Ype, GI:1245464 (Bearden and Perry 1999; Bearden et al 1998); ZnuA_Cje, GI:384442496 (Davis et al 2009); ZnuA_Eco, GI:298380994 (Patzer and Hantke 1998); ZnuA_Hin, GI:16272089 (Lu et al 1997); ZnuA_Sen, GI:161353595 (Ammendola et al 2007; Ilari et al 2011); ZnuA_Syn, GI:38492833 (Banerjee et al 2003); ZnuA_Tpa, GI:378974662 (Desrosiers et al 2007); ZnuA_Vpa, GI:28901162 (Gribenko et al 2013); ZnuA_Ype, GI:22126135 (Bobrov et al 2014); ZnuA_Yru, GI:238754865 (Dahiya and Stevenson 2010); YcdH_Bsu, GI:2415736 (Gaballa and Helmann 1998; Gaballa et al 2002). …”
Section: Figurementioning
confidence: 99%
“…The sequences of the 38 SBPs included in this study were obtained from the NCBI and had the following GI numbers: AdcA_Spn, GI:116516060 (Bayle et al 2011); AdcAII_Spn, GI:116515739 (Bayle et al 2011; Loisel et al 2008); FimA_Spa, GI:504525723 (Oetjen et al 2002); Lbp_Spy, GI:16151821 (Linke et al 2008; Linke et al 2009); Lmb_Sag, GI:22537388 (Ragunathan et al 2009a; Ragunathan et al 2009b); MntA_Ban, GI:229264967 (Gat et al 2005); MtsA_Sag, GI:22537676 (Bray et al 2009); MtsA_Spy, GI:383493478 (Sun et al 2009; Sun et al 2008); MntC_Ngo, GI:59800624 (Lim et al 2008); MntC_Sau, GI:88194402 (Horsburgh et al 2002a); MntC_Syn, GI:1653002 (Adir et al 2002); MtsA_Sin, GI:343481042 (Zou et al 2010); MtuA_Sub, GI:222113460 (Banerjee et al 2003); PsaA_Spn, GI:116515973 (McDevitt et al 2011); ScaA_Sgo, GI:310633 (Jakubovics et al 2000; Kolenbrander et al 1998); SitA_Eco, GI:84060846 (Sabri et al 2006); SitA_Sen, GI:16761638 (Zhou et al 1999); SitA_Sme, GI:15966779 (Chao et al 2004; Davies and Walker 2007; Platero et al 2004); SitA_Sps, GI:10135086 (Abate et al 2014); SitC_Sep, GI:57636840 (Cockayne et al 1998; Massonet et al 2006); SloC_Smu, GI:8925939 (Paik et al 2003); SsaB_San, GI:153826 (Crump et al 2014); TroA_Ssu, GI:386583456 (Wichgers Schreur et al 2011; Zheng et al 2011); TroA_Tpa, GI:1777933 (Deka et al 1999; Desrosiers et al 2007; Lee et al 1999; Lee et al 2002); YfeA_Ype, GI:1245464 (Bearden and Perry 1999; Bearden et al 1998); ZnuA_Cje, GI:384442496 (Davis et al 2009); ZnuA_Eco, GI:298380994 (Patzer and Hantke 1998); ZnuA_Hin, GI:16272089 (Lu et al 1997); ZnuA_Sen, GI:161353595 (Ammendola et al 2007; Ilari et al 2011); ZnuA_Syn, GI:38492833 (Banerjee et al 2003); ZnuA_Tpa, GI:378974662 (Desrosiers et al 2007); ZnuA_Vpa, GI:28901162 (Gribenko et al 2013); ZnuA_Ype, GI:22126135 (Bobrov et al 2014); ZnuA_Yru, GI:238754865 (Dahiya and Stevenson 2010); YcdH_Bsu, GI:2415736 (Gaballa and Helmann 1998; Gaballa et al 2002). …”
Section: Figurementioning
confidence: 99%
“…The wcaJ gene, whose product is related to capsule formation, was only identified in human isolates. On the other hand, five genes, whose products are associated with iron uptake, including the sitABC operon, which is involved in iron uptake in Staphylococcus ( Massonet et al, 2006 ), were found in all K. gyiorum genomes analyzed here. The bcr gene ( alcS in Bordetella spp. )…”
Section: Resultsmentioning
confidence: 91%
“…That may be related to the fact that intravenous iron therapy may result in nontransferrin-bound iron [18]. Although human cells have many ways of importing iron, the free ionic iron concentration in the human body is usually kept at a very low level to limit bacterial growth [19]. Therefore, it was not surprising that bound iron stores as measured by serum ferritin was not a significant variable distinguishing between those who were infected (mean ferritin 486.4 ± 354.0 mg/dl and those who were not (518.0 ± 423.0 mg/dl; table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was not surprising that bound iron stores as measured by serum ferritin was not a significant variable distinguishing between those who were infected (mean ferritin 486.4 ± 354.0 mg/dl and those who were not (518.0 ± 423.0 mg/dl; table 1). While pathogenic bacteria have developed powerful mechanisms that are capable of chelating iron at very low concentrations, 25 µ M of FeCl 3 has a significant effect on gene expression in biofilm-associated Staphylococcus epidermidis [19]. Similarly, since dextran molecules may resist protein adhesion by repulsive steric effects or hydration pressure, it may be associated with less infection than sucrose [20].…”
Section: Discussionmentioning
confidence: 99%